Hypnosis in the control of pain and anxiety in Pediatric Dentistry: a literature review - Susana Aguiar SANTOS; Rogério GLEISER; Thiago Machado ARDENGHI (Faculdade São Leopoldo Mandic, 2019)
This study is a literature review on the physical and mental influence of hypnosis in pediatric patient in controlling anxiety and pain. The objective was to gather the evidence found in the analysis of articles, research and systematic reviews, in the period from 1994 to 2018. For a descriptive review were selected Internet portals as Medicine®, Pubmed, Capes, using keywords like: "hypnosis", "pediatric dentistry", "fear", "anesthesia", "anxiety", "children", "pain". Descriptively and concisely, they presented relevant findings regarding associations between hypnosis and dentistry and their applications in controlling anxiety and pain. It was concluded that hypnosis could increase the cooperation of the child patient and decrease the resistance during painful dental procedures. Despite the promising results observed, hypnosis in pediatric dentistry is still seldom used. This may be due to lack of knowledge about the procedure and the absence of formal education, indicating the importance of including Hypnosis in the healthcare professionals' curriculum and their practices.